Conversion Of Religion In Muslim Marriage Lives: CONVERSION OF RELIGION IN MUSLIM MARRIAGE LIVES - Agoes Dariyo (Psikis : Jurnal Psikologi Islami, 2021)
This study aims to provide an overview of religious conversion in Muslim marital life. The research used a qualitative approach. The Data collected by interviews, and observation. The number of research subjects was 5 people (1 male and 4 female). The analysis technique is achieved by a triangular approach that involves interviews, observations, and theoretical concepts. The results showed that 2 factors were influencing religious conversion, marriage, and economic factors. Subjects experienced religious conversion through a gradual process, a period of calm, conflict, religious conversion, calm, and a period of expression of religious conversion.